Rescue Endovascular Treatment for Emergent Large Vessel Occlusion With Underlying Intracranial Atherosclerosis: Current State and Future Directions - Al Kasab, Sami; Almallouhi, Eyad; Spiotta, Alejandro M. (Frontiers in Neurology, 2021)
Intracranial atherosclerosis (ICAS) is one of the most common causes of stroke worldwide and is associated with high risk of stroke recurrence. While the most common clinical presentation is acute-subacute transient ischemic attack or ischemic stroke, occasional patients with underlying ICAS present with acute occlusion of the affected vessel. Diagnosis and endovascular management of ICAS related emergent large vessel occlusion can be challenging. Herein, we review the current evidence supporting endovascular management of ICAS related ELVO and what future directions should focus on.